Study on Micro-nano Fiber Coupled Ring Mirror and Its Spectral Controllability - GUO Chuanchen; YANG Min; CUI Qianqian; LIN Zheng; WEI Shilei; SUN Jiajia; LI Lijun (Guangtongxin yanjiu)
【Objective】Based on the micro-nano fiber coupler, this paper proposes a micro-nano fiber coupled ring mirror structure. Theoretical simulations and experimental studies are conducted to investigate the relationship between its spectrum and the polarization state of light within the ring mirror, the length of the micro-nano fiber in the tapered region, and the refractive index of the surrounding medium.【Methods】Theoretically, the basic principle of micro-nano fiber coupler is analyzed, and the optical field distribution of micro-nano fiber coupling and the spectral polarization of micro-nano fiber ring mirror are simulated. Experimentally, the spectral controllability is verified.【Results】The results show that when the half-wave plate angle of the circular polarization controller is adjusted at －90～90°, the period and the peak wavelength remains constant. The extinction ratio changes regularly with the angle and reaches the minimum at 45°, as well as the maximum at 90°. As the length of the waist cone increases, the channel interval and the free spectral range of the ring mirror comb spectrum presents gradually decrease. As the surrounding refractive index varies in the range of 1.332 0 to 1.335 5, the output interference wavelength is red-shift with 18 350 nm / RIU sensitivity.【Conclusion】In summary, by adjusting the polarization state of the coupled light inside the micro-nano fiber coupler, the length of the micro-nano tapered region, and the refractive index surrounding the coupler structure, corresponding changes in the output spectrum can be achieved. This provides a new approach for constructing novel all-fiber devices. These devices can not only be used as wavelength selection and regulation components in lasers to optimize laser output characteristics, but also applied in sensing fields such as biomedicine for high-precision detection of liquid components.